Quality of life & functional outcome of open tibial fracture managed with Ilizarov external fixator as definitive management - Ezekiel, George; Mohd Yusof, Nazri; Tasarib, Rohaman (IIUM Press, 2021)
The Ilizarov method is a useful tool for the treatment of the open tibial fracture. Many patients showed enormous resilience with this method of definitive fixation despite the devastating effects of their injuries. Our aim is to evaluate the value of IEF treatment for trauma patients with a focus on their quality of life as well as the functional outcome. A cross-sectional study was conducted across three years involving 109 patients with an open tibial fracture who underwent early Ilizarov external fixation as definitive management. Their quality of life after treatment was measured with an SF-36 health survey where else patient's functional and radiological outcomes were assessed using the Association for the Study and Application of Methods of Ilizarov (ASAMI) criteria. 88 (80.7%) of the participants had the site of initial fracture over the tibial shaft, 13 (11.9%) over the distal tibia and 8 (7.3%) of the participants had fracture over proximal tibia. 87 (79.8%) of the participants had Gustillo IIIa tibia fracture and 22 (20.2%) had Gustillo IIIb fracture. Clinical outcome was excellent in 76 (69.7%) good in 26 (23.9%) fairs in 5 (4.6%) and poor in 2 (1.8%) of the participants. Bone results were excellent in 84 (77.1%) good in 15 (13.8%) fairs in 8(7.3%) and poor in 2 (1.8%) of the participants. 106 (97.2%) patients achieved bone union. The results of the SF-36 Health Survey showed a significant difference between the population norm and the mean of the study group in Physical Functioning and Role Limitation-Emotional Problem. Early application of the Ilizarov fixator constitutes excellent management of open tibial fractures due to good functional and radiological results. The SF-36 Health Survey demonstrate that patients suffer mainly from physical and emotional sequel after this management nevertheless their general, mental, and social health is well preserved.